Academic hardiness in students who are working on thesis - Wati, Widia; Ifdil, Ifdil (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research is motivated by the phenomenon that final students who are working on their thesis experience excessive anxiety when working on their final assignment (thesis), this is because final students have low academic hardiness. The type of research used is descriptive quantitative. The sample in this study were active students of the 2018 FIP UNP Department of Curriculum and Educational Technology who were working on a thesis. A total of 77 students were selected using a porposive sampling technique, with the criteria of active students from the 2018 FIP UNP Department of Curriculum and Educational Technology who were working on essay. Data collection used the Likert scale model of the academic hardiness instrument. The results of the study revealed that: 1) academic hardiness of students from the Department of Curriculum and Educational Technology in 2018 who were working on a thesis based on the aspect of commitment was in the high category with a percentage of 63.64%, 2) academic hardiness for students of the Department of Curriculum and Educational Technology entering 2018 who are working on a thesis based on the control aspect is in the high category with a percentage of 55.84%, 3) academic hardiness for students of the Department of Curriculum and Educational Technology entering 2018 who are working on a thesis based on the challenge aspect is at very high category with a percentage of 42.86%.